PARADIGMA HASAN LANGGULUNG TENTANG KONSEP FITRAH DALAM PENDIDIKAN ISLAM - ARHAM JUNAIDI FIRMAN (Universitas Muhammadiyah Prof Dr Hamka, 2017)
Human in the process of creation is equipped with a set of abilities that have a tendency to develop. Hasan Langgulung’s thougth the study was conducted to see about the study of fitrah in the perspective og thinking of an Islamic educational figure. The objective of this research was to examine Hasan Langgulung’s thinking about the concept of fitrah in Islamic studies in more deeply. This research used library research method with historical and philosophical approach. This research showed: Langglung was born in Rapang, South Sulawesi on October 16, 1934 and died on August 2, 2008 in Kuala Lumpur, Malaysia. Hasan Langgulung says that fitrah are divine attributes in the human self that contained in Asma’ul Husna and it brought from their birth. According to Hasan Langgulung the effort of developing fitrah is the task of Islamic eduaction to transform it into the abilities that can be enjoyed by humans. Keywords: Hasan Langgulung, Fitrah Concept, Islamic Education